Penyelenggaraan Turnamen SSB sebagai Upaya Pembinaan Sepak Bola Usia Dini di Nagari Muaro Takung - Wawan Wahyudi; Sabrina Syifaussholiha; Nurhaliza Tarihoran; Togos Parmohonan; Aldo Rado; Randi Purnama Putra (Al-DYAS, 2026)
Although early-age football coaching plays an important role in developing athletes’ potential, the limited availability of structured competitions in Nagari Muaro Takung has resulted in low match opportunities for players, making the coaching process less than optimal. This study aims to describe the organization of a Football School tournament as an effort to support early-age football coaching through the utilization of community potential. This study used a descriptive qualitative approach with a case study design based on the Asset-Based Community Development approach. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, analysis, and conclusion drawing. The results show that the tournament successfully involved six Football Schools with a total of 12 participating teams. The round-robin system was applied in the U-10 category, while the U-12 category used a half-competition system followed by a knockout stage. The implementation of the tournament was supported by collaboration among KKN students, the nagari government, youth organizations, Football School administrators, match officials, and the community. This tournament provided more equal playing opportunities, improved players’ match experience, technical skills, and sportsmanship, and strengthened synergy among stakeholders in early-age football coaching. The conclusion of this study affirms that organizing a Football School tournament based on the Asset-Based Community Development approach can serve as an effective coaching model through the optimization of local assets. The implications of this study show that community collaboration and the application of a competition system suited to the characteristics of early-age players have the potential to support the organization of sustainable competitions that can be replicated in other regions.